2012
DOI: 10.1093/nar/gks1328
|View full text |Cite
|
Sign up to set email alerts
|

A dual-site simultaneous binding mode in the interaction between parallel-stranded G-quadruplex [d(TGGGGT)] 4 and cyanine dye 2,2′-diethyl-9-methyl-selenacarbocyanine bromide

Abstract: G-quadruplexes have attracted growing attention as a potential cancer-associated target for both treatment and detection in recent years. For detection purpose, high specificity is one of the most important factors to be considered in G-quadruplex probe design. It is well known that end stacking and groove binding are two dominated quadruplex-ligand binding modes, and currently most reported G-quadruplex probes are designed based on the former, which has been proven to show good selectivity between quadruplexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…This result indicates that these DNA motifs do not have the proper groove conformation and cannot induce DMSB to assemble into dimers. In addition, our previous data have shown that DMSB could stabilize parallel c-myc-2345 G4 while antiparallel-stranded H22 G4 and duplex CT nearly could not, indicating that dual-site binding mode of DMSB also resulted in higher affinity to parallel G4 [19]. Further, we compare recognition ability of specific G4s by the dual-site binding mode of end-stacking.…”
Section: The Selectivity Of Dmsb Versus Different Dna Motifsmentioning
confidence: 68%
See 2 more Smart Citations
“…This result indicates that these DNA motifs do not have the proper groove conformation and cannot induce DMSB to assemble into dimers. In addition, our previous data have shown that DMSB could stabilize parallel c-myc-2345 G4 while antiparallel-stranded H22 G4 and duplex CT nearly could not, indicating that dual-site binding mode of DMSB also resulted in higher affinity to parallel G4 [19]. Further, we compare recognition ability of specific G4s by the dual-site binding mode of end-stacking.…”
Section: The Selectivity Of Dmsb Versus Different Dna Motifsmentioning
confidence: 68%
“…This result strongly suggests there are two different binding modes in the interaction between TG4T and DMSB, called D-mode (stage of monomer assembling to dimer) in the case of [DMSB]/[TG4T] > 3 and M-mode (stage of dimer disassembling to monomer) in the case of [DMSB]/[TG4T] < 3. Our group has revealed that DMSB adopt a dual-site simultaneous binding mode of TG4T [19]. These results suggest that in M-mode DMSB stacks on the 3 0 -end of TG4T in the form of monomer, whereas in D-mode, DMSB could bind to the G-quadruplex in two different modes simultaneously in the form of monomer and groove-binding in dimer.…”
Section: The Binding Of Dmsb With Tg4tmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, the Armitage group has observed that the carbocyanine dye DiSC(3) binds to a folded intramolecular quadruplex with a 1:1 stoichiometry. 58 However, the nature of the cyanine dye is salient since another cyanine-based chromophore, DMSB, is also capable of binding to tetramolecular quadruplex DNA in a 2:1 fashion (where the dye forms a stacked homo-dimer) 59 . The incorporation of such cyanine based homodimers, or even chromophore tethered quadruplex DNA binding ligands (such as Distamycin A) 60 that bind to quadruplex DNA with higher stoichiometry, may allow for further enhancement of the amount of light energy funneled into the porphyrin acceptor within the nanowire scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…1), have been given particular attention in recent years. A higher sensitivity to environment and fluorescence enhancement effect of ETC for binding with biomolecules makes it be widely used in non-covalent label, [7] diagnostic probe [8] and DNA sequences applications, [16,17] and so on. The complexes of anticancer drugs and Tf are taken up by the cells through receptor-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%